Penerapan Hukum Keluarga Muslim di Asia Tenggara: Sebuah Perbandingan - Ahmad Khoirul Anam (Jurnal Bimas Islam, 2017)
Family law applied in a country shows how the religion position in the legal system and government in the country. Marriage and its intricacies are state affairs, as well as religious affairs. So the issue of family law is almost always a land of contention for the state and religion. The following article will compare the Muslim family law application in countries in Southeast Asia, the most populous Muslim region in the world. How is the Islamic law application in Muslim-majority countries such as Indonesia, Malaysia and Brunei Darussalam? How is the Muslim family law application in Muslim countries such as Singapore, the Philippines and Thailand, and the fate of the Muslim community in the Indo-China region: Myanmar, Vietnam, Cambodia and Laos. The condition of the "Islamic center" in the Middle East is being plagued by armed conflict, allowing the world to turn its attention to the Southeast Asian region. Hukum keluarga yang diterapkan di suatu negara menunjukkan bagaimana posisi agama dalam sistem hukum dan pemerintahan di negara tersebut. Perkawinan dan seluk-beluknya adalah urusan negara, sekaligus urusan agama. Maka persoalan hukum keluarga hampir selalu menjadi lahan rebutan bagi negara dan agama. Artikel berikut ini akan membandingkan penerapan hukum keluarga Muslim di negara-negara di Asia Tenggara, kawasan berpenduduk Muslim yang sangat besar di dunia. Bagaimana penerapan hukum Islam di negara-negara mayoritas Muslim seperti Indonesia, Malaysia dan Brunei Darussalam? Bagaimana penerapan hukum keluarga Muslim di negara-negara berpenduduk minoritas muslim seperti Singapura, Filipina dan Thailand, serta bagaimana nasib komunitas Muslim di kawasan Indo-China: Myanmar, Vietnam, Kamboja dan Laos. Kondisi â€œpusat Islamâ€ di Timur Tengah yang sedang dirundung konflik bersenjata, memungkinkan dunia mengalihkan perhatian ke kawasan Asia Tenggara.